Fred Fearnot's New Ranch : and How He and Terry Managed It - Shackleford, H. K. (Harvey King), 1841-1906 (Salt Lake City, UT : Project Gutenberg, 2007)
"Fred Fearnot's New Ranch" by H. K. Shackleford is a novel written in the early 20th century. The story follows the adventures of Fred Fearnot and his friend Terry Olcott as they navigate life in Wall Street before heading back to manage their new ranch in Texas. Their journey involves handling personal conflicts, establishing romantic relationships, and developing their ranching operations while facing the challenges of the American West. The opening of the novel sets the stage with Fred and Terry in Wall Street, where they reflect on their recent financial dealings and the fallout from a confrontation with a rival broker. Their success leads them to leave the excitement of the city in favor of a quieter life on their ranch. The narrative quickly shifts to their return to Texas, where they discuss plans for expanding their cattle herd and building a home for their sweethearts. The introduction of characters like Evelyn and Mary hints at romantic subplots, while the dynamic between the characters promises an engaging blend of adventure, rivalry, and burgeoning romance as they settle into ranch life. (This is an automatically generated summary.)
Release date is 2007-06-10
E-text prepared by Richard Halsey
Keywords: Adventure stories; Young men -- Juvenile fiction; Ranch life -- Juvenile fiction